2022
DOI: 10.1002/art.42245
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Short‐Term Bridging Strategies With High‐ and Low‐Dose Prednisolone on Radiographic and Clinical Outcomes in Active Early Rheumatoid Arthritis: A Double‐Blind, Randomized, Placebo‐Controlled Trial

Abstract: Objective. In active early rheumatoid arthritis (RA), glucocorticoids are often used for bridging, due to the delayed action of methotrexate. This study was undertaken to compare the effect of 3 bridging strategies, including high-dose and low-dose prednisolone, on radiographic and clinical outcomes.Methods. Adult RA patients from 1 rheumatology hospital and 23 rheumatology practices who presented with moderate/high disease activity were randomized (1:1:1) to receive 60 mg prednisolone (high-dose prednisolone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Trying to avoid adverse effects of GC could affect achieving the benefits of GC. The recent CORRA trial showed that after a ‘COBRA light schedule’ that tapered to zero in 3 months, no radiological benefit could be shown 34. For now, it remains unclear which is the best bridging schedule when balancing both safety and efficacy, and which (cumulative) dose of GC gives an increased risk of adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Trying to avoid adverse effects of GC could affect achieving the benefits of GC. The recent CORRA trial showed that after a ‘COBRA light schedule’ that tapered to zero in 3 months, no radiological benefit could be shown 34. For now, it remains unclear which is the best bridging schedule when balancing both safety and efficacy, and which (cumulative) dose of GC gives an increased risk of adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of Arthritis & Rheumatology , Krause et al describe a large placebo‐controlled trial examining the potential benefit of short‐term GC bridge therapy on structural damage in RA (14). The study was adequately powered for a difference of 2 Sharp/van der Heijde units and was meticulously conducted, but it was unable to show benefit of up to ~1,400 mg oral prednisolone over 12 weeks.…”
Section: Figurementioning
confidence: 99%
“…The severity of RA varies, and treatment typically involves the use of one or a combination of immunomodulators, commonly referred to as disease-modifying anti-rheumatic drugs (DMARDs) [1]. Acute-phase reactant data, particularly regarding the erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), and the disease activity score 28 (DAS28), are crucial in predicting prognosis and guiding treatment [2][3][4][5]. Disease activity indices are also pivotal in assessing the effectiveness of treatments in clinical trials.…”
Section: Introductionmentioning
confidence: 99%